Literature Review: Pengaruh Stres Kerja Terhadap Kinerja Perawat di Rumah Sakit - Diwani Br Barus, Dila; Susilawati, Susilawati (Cantaka: Jurnal Ilmu Ekonomi dan Manajemen, 2024)
Hospitals as a place of health service are required to provide the best and maximum service possible. Nurses are one of the medical personnel in hospitals who can provide services to provide care to patients and support patient health. In carrying out their work, nurses often experience pressure. They are expected to remain professional and provide quality services to patients. The more demands one faces, the higher the stress level. Researchers used a literature review approach as a means to identify and evaluate the level of work stress experienced by nurses on their performance in the hospital. The population and sample in question are relevant journals and articles that discuss the implementation of work stress levels and nurse performance. Searches and sources when compiling a survey about this research utilized web resources, namely Google Scholar and Semantic Scholar. From the review that has been carried out, it can be concluded that work stress influences the performance of hospital nurses. This can be caused by many factors, including excessive workload, stress and pressure from both patients and superiors, conflicts with colleagues, and an uncomfortable work environment. Therefore, effective stress management such as training in relaxation techniques, social support, fair division of tasks, and supportive work environment policies can help reduce the negative impact of work stress on nurse performance.